COVID-19 VACCINATION ACCEPTANCE AMONG PRECLINICAL AND CLINICAL MEDICAL STUDENTS - Maksimović, Katarina; Grujičić, Sandra; Ilić Živojinović, Jelena; Tomanić, Milena; Vujčić, Isidora (HEALTH CARE, 2025)
Introduction/Aim. Health workers and medical students played an important role in the COVID-19 pandemic, so their responsibility, knowledge and attitudes towards vaccination were very important in the pandemic. The aim of this study was to examine COVID-19 vaccination acceptance among medical students according to their study year.Methods. In this cross sectional study 730 students of the Faculty of Medicine of the University of Belgrade participated, of which were 332 preclinical students (45.5%) and 398 (54.5%) clinical students. The study was conducted between December 1, 2022 and January 31, 2023 based on a specially designed questionnaire, which the students filled out anonymously and on a voluntary basis.Results. The largest number of students declared that they have never been infected with COVID-19 (63.0%). Clinical students were significantly more vaccinated (94.5% vs 87.3%, p=0.001). As the most common reasons for vaccination, students state the desire to protect the people around them (64% preclinical and 71% clinical, p=0.594), availability of vaccine (27% preclinical and 33% clinical, p=0.407) and recommendation by healthcare workers (30% preclinical and 27% clinical, p=0.111). The most common reason for not receiving the vaccine were the suspicion that the vaccines have not been tested enough (52% preclinical and 59% clinical, p=0.407) and the fear of side effects (26% and 50%, p=0.059). Clinical medical students significantly more often regularly followed information about COVID-19 vaccine and received information from the Internet in comparison with preclinical students.Conclusion. The obtained results show a high coverage of vaccination among preclinical and clinical medical students. Timely and accurate information through the media and social networks can contribute to preventing misinformation and help the public health system in future challenges and campaigns.
Keywords: COVID-19, medical students, vaccine